Examining the Role of Trust and Informal Communication on Mutual Learning in Government: The Case of Climate Change Policy in New York. (March 2017) - Temby, Owen; Sandall, Jean; Cooksey, Ray; Hickey, Gordon M.
Although public agencies must mutually coordinate climate policy and other complex environmental issues, the extent and relative importance of informal networks and different dimensions of trust to the process remains underresearched. Addressing this, we conducted surveys and interviews with civil servants from numerous agencies and three levels of government working on climate change–related policy in the state of New York. We examined the effect of two network properties on mutual learning on climate change–related issues: the extent to which interagency communication takes places through formal and informal channels, and the distribution of two dimensions of trust ("fair play" and "relational comfort") across the network. Our analysis revealed that formal communication among staff at different agencies was utilized more often than informal and that interagency relationships were more characterized by a feeling of "fair play" than by "relational comfort, " yet informal communication and Relational Comfort were the most important in facilitating interagency collaboration.